2015
DOI: 10.5380/abclima.v16i0.41149
|View full text |Cite
|
Sign up to set email alerts
|

Cenários Climáticos Futuros Para O Paraná: Oportunidades Para O Setor Florestal

Abstract: RESUMO:Esse trabalho se propôs a simular cenários climáticos futuros para o Paraná, bem como avaliar os projetos de base florestal no contexto de potenciais mudanças do clima. Foi obtida a série histórica diária da variável temperatura máxima do ar, temperatura média do ar, temperatura mínima do ar, precipitação e altitude de 45 estações meteorológicas dos anos 1970 a 2010 para o Paraná e estados de fronteira. Os dados representaram a base para a simulação de cenários futuros, realizada no software PGECLIMA_R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
2
2
0
1
Order By: Relevance
“…This socioeconomic effect was also observed in studies carried out on other continents [ 19 , 72 , 73 ]. Regions with higher development indices generally present a protection factor for cardiovascular diseases, a result corroborated by other studies in other countries in which socioeconomic differences represent a difference in the occurrence of cardiovascular diseases according to social class [ 63 , 64 ]. As for deaths caused by cardiovascular diseases, the MHDI had less impact on health outcomes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This socioeconomic effect was also observed in studies carried out on other continents [ 19 , 72 , 73 ]. Regions with higher development indices generally present a protection factor for cardiovascular diseases, a result corroborated by other studies in other countries in which socioeconomic differences represent a difference in the occurrence of cardiovascular diseases according to social class [ 63 , 64 ]. As for deaths caused by cardiovascular diseases, the MHDI had less impact on health outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…The maximum and minimum temperatures showed a tenuous and constant increasing tendency in most regions, and the relative humidity varied according to the region and the rainfall rates [ 64 , 65 , 66 ]. The climate of the study area, as well as that of Brazil, showed an increase in the thermal amplitude, making it possible to observe regional differences in climate and health outcomes, which was also observed by [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found byMelo, Sanquetta, Corte and Virgens Filho (2015) andSantos et al (2020) who observed air temperature increases in all climate scenarios projected for the Paraná State. Considering the more pessimistic scenario of the IPCC, the largest increases occurred in the northwest and northeast regions, and the smallest increases occurred in the central-southern region of Paraná.…”
supporting
confidence: 88%
“…Potential distribution modeling is an alternative tool for mapping potential areas for adaptation of species, using a smaller number of variables that would be required by the zoning method, making possible the extrapolation of species occurrence projections in future scenarios, according to global climate change (Bader et al, 2008;Melo et al, 2015). However, it has limitations and should be used in conjunction with other tools to aid decision-making (Garcia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%